To the Question of School Myopia - E. Y. Markova; N. A. Pron'ko; L. V. Aminulla; L. V. Venediktovа; L. Y. Bezmelnitsyna (Oftalʹmologiâ)
Refractive errors in children is one of the most important problems of ophthalmology. Over the past decades, the trend of increasingthe number of children with myopia and accommodation disorders continues to persist in the world. The present study was organizedto update data on the prevalence of refractive errors among schoolchildren in Moscow. The studied group included school-agechildren: pupils of 1, 5, 11 classes. The inclusion criteria were: myopia — refraction above –0.5 D, hypermetropia — refraction above +0.5 D, astigmatism above 0.5 D. The results of survey 1557 pupils from Moscow schools, the proportion of patients with refractive errors was 24–28%, while the proportion of patients with myopia among 1st class pupils was only 2%. In 5th class, the rate was 10%, in the 11th grade reached 23%, i.e. increased more than 10 times. Noteworthy is the fact that since the 5th class, there were differences in the prevalence of myopia in groups of boys and girls. It is significantly higher in girls. This can be explained by the fact that girls spend more time for learning process and with a faster growth rate of girls in these age periods. This pattern was also revealed in the 11th class, which undoubtedly indicates adverse visual influence of the training loads. The obtained data on the prevalence of refractive errors, including myopia, in children and adolescents, can be used as the basis for planning the measures of improving preventive eye care for children and young people